Exploring the mediating effect of feedback self-efficacy between students’ self-feedback behavior and academic proficiency - Yang, Yongle; Yan, Zi; Zhu, Jinyu; Guo, Wuyuan; Wu, Junsheng; Huang, Bingjun (Frontiers in Psychology, 2025)
Self-feedback and feedback self-efficacy are imperative components of self-regulated learning; few studies have investigated their combined impacts on academic achievement. This study examined the predictive effects of self-feedback behaviors, feedback self-efficacy, and academic proficiency using a questionnaire survey from 665 Chinese high school students across Chinese, English, and mathematics subjects. Structural equation modeling showed that only use feedback (UF) directly predicted academic proficiency, while both process feedback (PF) and use feedback (UF) demonstrated indirect effects mediated through feedback self-efficacy. At the same time, seek feedback (SF) was not a significant predictor in direct and indirect effect tests. Multi-group SEM analysis further explored gender differences in the effects; male students hold stronger predictive power of PF over feedback self-efficacy, while female students with feedback self-efficacy could achieve greater academic success. These results recognize the critical effects of feedback self-efficacy in translating students’ self-feedback behavior into their academic performance. The study empirically supports the self-system model and emphasizes the need for differentiated feedback instructional strategies among male and female students. It also contributes to scale studies of the recently published Self-feedback Behavior Scale (SfBS), by further supplementing evidence for its reliability and cross-gender applicability using a different dataset. The findings indicate that differentiated instructional strategies are necessary to empower students with more effective self-feedback strategies and personal beliefs; by doing this, students could better benefit from the feedback process and achieve substantial academic growth.